PETROGENETIC AND METALLOGENETIC BACKGROUND OF THE DAJING CU-SN-AG-PB-ZN ORE DEPOSIT, INNER MONGOLIA, AND CHARACTERISTICS OF THE MINERALIZING FLUID - Liu W.; Li X.-J.; Tan J. (My University, 2001)
The Dajing Cu–Sn–Ag–Pb–Zn ore deposit, Inner Mongolia of China, is a fissure-filling hydrothermal ore deposit that occurs within the Upper Permian Linxi group. No magmatic pluton and volcanic rocks outcrop on the surface of the deposit. Most of ore veins show clear-cut boundary with country rocks. Wallrock alterations that include silicification, carbonation, chlori–tization, and sericitization are generally weak and occur in the close vicinity of ore veins. Mineralization is divided into three stages: (1) cassiterite–arsenopyrite–quartz stage, (2) sulfide stage, and (3) Pb–Zn–Ag–carbonate stage. These mineralization stages have distinct ranges of homogenization temperatures, 290–350C for Stage 1, 260–320C for Stage 2, and 150–250C for Stage 3. However, salinities for Stages 1, 2, and 3 overlap and range between 2.2 and 10.4 wt % NaCl equivalent. The dD values relative to V-SMOW of inclusion water from quartz are lower than –88% and centered at –100 to –130%. The δ34S values relative to CDT of sulfide ore minerals and δ13C values relative to PDB of carbonate gangue minerals, vary from –0.3 to +2.6%, and from –7.0 to –2.9%, respectively. Integrated isotopic data point to two major contributions to the mineralizing fluid that include a dominant meteoric-derived water and the other from hypogene magma for sulfur and carbon species. Analyses of inclusion gas and liquid compositions are performed. The H2O and CO2 are the two most abundant gaseous components, whereas SO42- and Cl-, and Na+, Ca2+, and K+ are the major anions and cations, respectively. A linear trend is shown on the gaseous H2O versus CO2 plot. Phase separation is excluded as cause for the trend on the basis of isotope data and fluid inclusion microthermometry. In addition, a weak wallrock alteration does not support fluid-rock interaction as an efficient mechanism. Hence, the linear H2O–CO2 trend is interpreted in terms of absorption or dilution of CO2–dominant magmatic vapor by meteoric-derived water. Cooling effects resulting from dilution may have caused precipitation of ore minerals. Major and trace element compositions of regional granites show a high-K calc–alkaline characteristics and an arc–affinity. Lead isotopic compositions of galena samples from the Dajing deposit exhibit elevated U/Pb and Th/Pb ratios. These characteristics indicate a common source of supra subduction zone mantle wedge for regional granites and metals from the Dajing deposit.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская